Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1104/pp.110.167536
|View full text |Cite
|
Sign up to set email alerts
|

The Soybean Rhg1 Locus for Resistance to the Soybean Cyst Nematode Heterodera glycines Regulates the Expression of a Large Number of Stress- and Defense-Related Genes in Degenerating Feeding Cells      

Abstract: To gain new insights into the mechanism of soybean (Glycine max) resistance to the soybean cyst nematode (Heterodera glycines), we compared gene expression profiles of developing syncytia in soybean near-isogenic lines differing at Rhg1 (for resistance to Heterodera glycines), a major quantitative trait locus for resistance, by coupling laser capture microdissection with microarray analysis. Gene expression profiling revealed that 1,447 genes were differentially expressed between the two lines. Of these, 241 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 70 publications
(90 reference statements)
10
126
0
1
Order By: Relevance
“…RT was done using the Primescript first-strand cDNA synthesis kit (Takara, Clontech). Real-time quantitative RT-PCR was conducted as described by Kandoth et al (2011). Samples were normalized relative to the soybean ubiquitin gene (accession no.…”
Section: Rt Reaction and Qpcr Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…RT was done using the Primescript first-strand cDNA synthesis kit (Takara, Clontech). Real-time quantitative RT-PCR was conducted as described by Kandoth et al (2011). Samples were normalized relative to the soybean ubiquitin gene (accession no.…”
Section: Rt Reaction and Qpcr Assaysmentioning
confidence: 99%
“…Management relies heavily on the use of resistant soybean cultivars. In these cultivars, necrosis of the feeding site prevents the development of the sedentary nematode (Endo, 1965;Acedo et al, 1984;Mahalingam and Skorupska, 1996;Kandoth et al, 2011).…”
mentioning
confidence: 99%
“…These metabolites are involved in numerous vital processes such as plant defense, formation of structural biopolymers and cell wall components including lignin, lignols, defense related phenolics and the synthesis of hormones and vitamins. Phenolic compounds are involved in PCD (Program Cell Death) in response to SCN and F. virguliforme infections (Mahalingam and Skorupska, 1996;Yuan et al 2002;Iqbal et al 2008;Kandoth et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, many stress-related genes were upregulated in the soybean resistant line containing Rhg1 gene. These genes include those coding for the enzymes involved in the biosynthesis of ROS (Kandoth et al, 2011). Kandoth et al (2011) also indicated that the feeding sites induced by Heterodera glycines in the resistant line experienced severe oxidative stress coupled with imbalanced endoplasmic reticulum homeostasis, and both of these processes contribute toward the plant resistance.…”
Section: Host Transcriptomes In Response To Nematode Infectionmentioning
confidence: 99%
“…These genes include those coding for the enzymes involved in the biosynthesis of ROS (Kandoth et al, 2011). Kandoth et al (2011) also indicated that the feeding sites induced by Heterodera glycines in the resistant line experienced severe oxidative stress coupled with imbalanced endoplasmic reticulum homeostasis, and both of these processes contribute toward the plant resistance. So this is still debatable that whether the genes involved in the synthesis of ROS are important for compatible interactions or resistance response.…”
Section: Host Transcriptomes In Response To Nematode Infectionmentioning
confidence: 99%